Hybrid Sistem Algoritma Rivest Shamir Adleman (RSA) dan Algoritma Blum Blum Shub (BBS) dalam Mengamankan File Database E-Absensi - Tania Br Surbakti; Achmad Fauzi; Husnul Khair (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
The E-Attendance System has become an efficient solution in monitoring individual attendance at various institutions. However, new challenges arise regarding data security and privacy in managing E-Attendance database files. Facing potential risks such as hacking and data leaks, data security becomes very important. Therefore, in this study, we propose the implementation of a hybrid system that combines the strengths of the Rivest Shamir Adleman (RSA) Algorithm and the Blum Blum Shub (BBS) Algorithm to improve the security of the E-Absence database file. RSA is a cryptographic algorithm that is widely used for encryption and digital signatures. On the other hand, BBS is a random number generation algorithm that has a strong level of security. The combination of the two in the form of a hybrid system is expected to provide a higher level of security in securing E-Absence data. The aim of this research is to develop a hybrid RSA and BBS system in the context of securing E-Attendance database files. This research outlines the basic concepts of the two algorithms and how they can be integrated. The results of this study are the combination of the Rivers, Shamir, Adleman (RSA) algorithm and the Blum Blum Shub (BBS) algorithm in a hybrid system to increase security in the process of encoding messages